Pengaruh Kebijakan Dividen dan Investment Opportunity Set (IOS) terhadap Kinerja Perusahaan pada Perusahaan BUMN Go Public - Anggi Angga Resti; Budi Purwanto; Wita Juwita Ermawati (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
This research to determine the effect of devidend policy and Investment Opportunity Set (IOS) on the firm performance on state-owned enterprises (SOE) go public listed in the Indonesia Stock Exchange. The population in this study are all state-owned enterprises (SEO) go public listed on the Indonesia Stock Exchange in 2013-2017 as many as 20 companies. The method used is purposive sampling, with the number of samples observed as many as 13 companies. The data used in study is secondary data in the form of financial statements. The Structural Equation Modeling (SEM) was applied in this study to determine the effect of divident policy and Investment Opportunity Set (IOS) on firm performance. The result shows that divident policy has positive significant impact on the firm performance and Investment Opportunity Set (IOS) has not significant impact on the firm performance.